ANTHROPOLOGICAL DIMENSION OF THE PROBLEMS OF MODERN SOCIETY IN THE CONTEXT OF SCIENCE AND FREEDOM INTERRELATION - Скиба, І. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article investigates the modern society problems concerning the relations between science and freedom from the human-like per-spective. Introduction. The author identifies the specifics of modern society, focuses on trends of its development, existing problems that actualize the subject of this study. The aim and tasks. The author explores the anthropological problems of modern society. Among the tasks is exploration the problems of freedom as the basis of any social development and science (scientific knowledge) as the main factor of modern social development. Research methods: systematic, cultural-historical and sociocultural methodological approaches are used in their dialectical interconnection. Research results: problems of society nowadays are increasingly acquiring anthropocentric, even sense-oriented coloring. The latter, in its turn, is connected with the values and freedom in man’s life. A change in social development strategy is also a consequence of the choice of “critical mass” of people rather than one person. The choice is al-ways made at the level of values and worldview. Therefore, the role of worldview disciplines is significantly increasing in the modern world. The modern problem of freedom is acquiring some peculiarities resulting from the processes of informatization and globalization, consumption strategies, the emergence of virtual reality and a virtual personality, and others. Freedom is integrated into the system of knowledge, immanently corresponds to its anthropological factors, and it is also directly proportional to the result obtained. Such a choice is possible if there is awareness of it, otherwise it withdraws from freedom and approaches chance and “blind” determinism. The-se days, both in the life of an individual and a society, the decisive role is given to scientific knowledge. On the one hand, it is the main factor of social development, since it is scientific knowledge that has the greatest influence on civilization choice. On the other hand, in modern social practices including the technical sphere there is a tendency of reduction of the status of science. It is manifested in the fact that scientific-technological progress is coming to replace scientific-technical one, that transforms the classical way of interconnec-tion of science, technics and technology. At the same time, the development of postnonclassical rationality takes place inside the sci-ence itself, that combined with the formation of a synergistic picture of the world, is preparing new responses to the challenges of the modern world. Discussion The author more broadly refers to the conception of the dependence of freedom on knowledge. In particular, the views of B. Spinoza, M. Polani, M. Weber and others are considered. Conclusion. The current stage of the society development poses many challenges, threats and risks to humanity. Most of them point out to the anthropological crisis as their root cause. Certain results of social development (positive or negative) simultaneous and always are the consequences of a certain socio-cultural choice. Exclusively investigating and understanding the reason allows one to make another choice consciously, including one that is compatible with life.